296. A BEGINNER'S THREE-YEAR LEARNING CURVE WITH ESOPHAGECTOMIES: A STUDY FROM A PERIPHERAL CANCER CENTRE IN NORTH-EAST INDIA. (24th September 2022) - Das, Gaurav
Abstract: North-East India has a high incidence of esophageal cancer but lacks good infrastructure for cancer care delivery. I aim to present my experience with esophagectomies done in a cancer center of the region, as a beginner immediately after completion of broad specialty surgical oncology training. The objectives include estimation of 30-day morbidity and mortality rates and the short-term oncological outcomes including nodal yield and completeness of resection. Retrospective observational study of a prospectively maintained database, during the study period from 1st November 2018 to 31st March 2022 (29 months). All patients had confirmed diagnosis of esophageal cancer and underwent esophagectomy by the same surgeon. They received neoadjuvant treatment as per institutional protocol. The results were presented with median values, range and percentages. 46 patients underwent esophagectomy; one had inoperable disease. Clinicopathological factors are in Table 1. 74.5% had neoadjuvant chemoradiation (NACRT). Minimally invasive trans-thoracic esophagectomy (67.4%) was favoured approach (conversion rate of 6%). 41.3% had 'extended 2-field' lymphadenectomy. 30-day mortality was 4.2% and morbidity included hoarseness of voice (17.4%), anastomotic leak (10.9%) and pneumonia (8.7%). Median nodal yield was 12 (range 4 to 48). Pathological complete response was noted in 44.1% of post-NACRT patients. Margin-negative resection was achieved in 91.3% patients. After median follow up of 20 months, 5 locoregional and 3 distant recurrences were noted. 76.6% patients are alive without disease. Surgical audit is key at the beginning of a surgical career to gain insights into learning curve and areas of improvement include nodal yield and morbidity rates. The high margin negative resection rates are partly attributable to selection bias of a beginner.